Extracorporeal Membrane Oxygenation for Hemodynamic Support of Ventricular Tachycardia Ablation. (December 2016) - Baratto, Francesca; Pappalardo, Federico; Oloriz, Teresa; Bisceglia, Caterina; Vergara, Pasquale; Silberbauer, John; Albanese, Nicolò; Cireddu, Manuela; D'Angelo, Giuseppe; Di Prima, Ambra Licia; Monaco, Fabrizio; Paglino, Gabriele; et al.
Abstract : Background—: We report the experience in a cohort of consecutive patients receiving extracorporeal membrane oxygenation during catheter ablation of unstable ventricular tachycardia (VT) at our center. Methods and Results—: From 2010 to 2015, extracorporeal membrane oxygenation was initiated in 64 patients (average age: 63±15 years; left ventricular ejection fraction in 27±9%; cardiogenic shock in 23%, and electrical storm in 62% of patients) undergoing 74 unstable VT catheter ablation procedures. At least one VT was terminated in 81% of procedures with baseline inducible VT, and VT noninducibility was achieved in 69%. Acute heart failure occurred in 5 patients: 3 underwent emergency heart transplantation, 1 had left ventricular assist device (LVAD) implantation, and 1 patient eventually died because of subsequent mesenteric ischemia. All other patients were discharged alive. After a median follow-up of 21 months (13–28 months), VT recurrence was 33%; overall survival was 56 out of 64 patients (88%). Extracorporeal membrane oxygenation–supported ablation was the bridge to LVAD in 6.9% and to heart transplantation in 3.5% of patients. VT recurrence was related to ablation success (after 180 days of follow up: 19% when VT was noninducible, 42% if nonclinical VT was inducible, 75% when clinical VT was inducible, and 75% in untested patients, P <0.001). Incidence of all-cause death, heart transplantation, and LVAD was independently related to ablation outcome (at 180 days of follow-up: 9% when noninducibility was achieved, 50% in case of inducible VT, and 75% in untested patients, P <0.001). At multivariable analyses, noninducibility (hazard ratio 0.198; P =0.001) and left ventricular ejection fraction (hazard ratio 0.916; P =0.008) correlated with all-cause death, LVAD, and heart transplantation. Conclusions—: Ablation of unstable VTs can be safely supported by extracorporeal membrane oxygenation, which allows rhythm stabilization with low procedure mortality, bridging decompensated patients to permanent LVAD or heart transplantation. Successful ablation is associated with better outcomes than unsuccessful ablation.